Quantitative ethnobotany of medicinal plants used by the Bodo Community of Baksa District, BTR, Assam, India - MIJING BORO; BARNALI DAS; KRISHNA KUMAR BORO; MADHUSHMITA NATH; PRIYAKSHI BURAGOHAIN; SHILPA ROY; PARAG JYOTI SARMA; SUSHMITA KALITA; NAMITA NATH (Society for Indonesian Biodiversity, 2023)
Abstract. Boro M, Das B, Boro KK, Nath M, Buragohain P, Roy S, Sarma PJ, Kalita S, Nath M. 2023. Quantitative ethnobotany of medicinal plants used by the Bodo Community of Baksa District, Assam, India. Biodiversitas 24: 3169-3182. Plants are the core part of religious and cultural aspects of various ethnic communities of the world. Assam is a homeland of diverse ethnic tribes of Indo-Mongolian origin. The Bodo Community is one of the oldest communities and they are rich in their traditional healthcare knowledge system. The current study aimed to record the data on medicinal plants used by the Bodo Community in Baksa District, Assam, India. Statistical analysis was done by following established formula to find Use Value (UV), Relative Frequency of Citation (RFC), Informant Agreement Ration (IAR) and Informant Consensus (Fic). A total of 129 medicinal plant species were recorded, used in 18 different ailment categories by the Bodo people. Kalanchoe pinnata (Lam.) Pers. was the most used plant by the informants (use value 0.69) and also had the highest RFC (0.60). In present survey, the IAR range was from 0-1. The highest Fic value was recorded in the ailment category of Renal and hepatic disorder. The present work provides rich data, as this work, besides documenting the medicinal plants used by the community, also gives proper scientific evaluation of the ethnobotanical data. The work will be helpful for future researchers, academicians and stakeholders to carry out research work in this diverse scientific field of ethnobotany. From the conservation point of view, there is an urgent need to involve local people for the conservation of medicinal plants for the future.